BEYOND REPRESENTATION: HOW KNOWLEDGE UTILISATION TRANSLATES BOARD GENDER DIVERSITY INTO CORPORATE PERFORMANCE - SABSOMBAT, Nuthawut; SURALAI, Wiparat (Asian Administration and Management Review, 2025)
This study investigates the intricate relationship between board gender diversity and corporate performance within Thai firms, challenging the assumption that mere representation automatically translates into improved outcomes. Employing a quantitative approach with survey data from 150 companies and qualitative insights from director interviews, the research examines the mediating role of board knowledge and skill utilization. Results indicate a complex dynamic: while gender diversity alone correlates negatively with corporate performance measured by the Balanced Scorecard (BSC), it positively influences board knowledge and skills utilization. This enhanced utilization, in turn, drives improved corporate outcomes across financial, customer, internal process, and learning and growth perspectives. The findings highlight the importance of fostering inclusive engagement and knowledge-sharing within boards to unlock the strategic benefits of diversity, contributing to a more nuanced understanding of corporate governance in emerging Asian markets.